CIVILIZATION AFTER THE CRUSADES(The Impact of the Crusades on Civilization, Commentary of Modern-day Scholars and Efforts to Prevent Decadence) - M. KHIKAMUDDIN; NURUL HIKMAH (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2022)
This research examines the history of the Crusades and their impact on Islamic civilization and the thinking of ulama in the modern era. The Crusades were a series of conflicts that began with religious motives and turned political and economic. Regarding zonation, the Crusades were initially centered around Jerusalem, then spread to various other areas and took place between 1096 and 1365 AD. The focus of the study in this article includes: (1)History and factors that led to the Crusades, (2)Periodization of the Crusades, (3)The impact of the Crusades on the progress of Western nations and the decadence of civilization in the East, (4)Thoughts on the continuing gap between Islam and Christianity after the Crusades and (5)What Muslims should do to prevent the decadence of civilization. Through qualitative research methods with a literature review, this research found several conclusions: (1)The Crusades manifested European expansionism. (2)The Crusades had several significant impacts on the progress of European nations; (3)The Islamic world experienced decadence in various areas of life due to this series of events, both in Andalusia, Baghdad, Jerusalem, and other Islamic regions, (4)Even though the Muslims were successful defending most of its territory from attacks by the crusaders, the losses they suffered were very large. The Islamic world has been hit by various religious, political, socio-economic, educational, and cultural crises. These losses resulted in the weakening of the political power of Muslims, which further worsened the condition of division (5)Even though the Crusades ended several centuries ago, stereotypes of Muslims and even ulama in the modern era consider that every religious conflict is an extension of The Crusades. This research is very useful in providing a horizon for reading major conflicts between religious communities and the motives behind religious interests, as well as things that Muslims need to pay attention to so that they are always alert to all forms of attacks in the name of religion.